Makna Denotatif dsan Konotatif dalam Puisi Fakkir Bighairik Karya Mahmoud Darwish: Kajian Semantik - Muhammad Muhammad; Sayyed Zuhdi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines the denotative and connotative meanings in Mahmoud Darwish's poem